USER REQUIREMENT FOR WEB-BASED PROCEEDINGS REPOSITORY (Journal of Digital System Development, 2024)
Conference is a popular platform for academics to exchange knowledge and engage with one another. The conferences typically produce collections of papers, known as conference proceedings, which are often published online as open-access resources to facilitate more comprehensive access and dissemination of knowledge. Consequently, there has been a significant increase in articles on online conference proceedings. However, the absence of an organised management system has made it increasingly challenging for users to locate and retrieve specific proceedings. To address this issue, this study proposes implementing a digital repository system to simplify the sharing and distributing of conference proceedings articles. The primary goal of this project is to provide a sustainable solution for storing and accessing conference proceedings, characterised by its reliability, efficiency, effectiveness, and user-friendliness. Such an enhancement is anticipated to boost research productivity and quality. In this article, we present the system requirements for the repository. Subsequently, based on these requirements, we have developed a prototype called the Web-based Digital Repository for Proceedings Articles (WDR). We conducted a field study to assess the prototype's usability, and the evaluation results indicate that WDR is both practical and user-friendly.